Desain Agro Park Ruang Terbuka Hijau Kecamatan Tomilito - Zuhriati A. Djailani; Sri Sutarni Arifin (Universitas Negeri Gorontalo, 2021)
ABSTRACT.Green open space (GOS) as the lungs of the city is one aspect of the ongoing recycling function between carbon dioxide (CO2) and oxygen (O2) gases. Other functions of green open space include aesthetic functions, recreation and space for social interaction between communities. The Green Open Space Agro Park in Tomilito District, North Gorontalo Regency aims to create a more quality, beautiful, comfortable, organized, healthy and sustainable urban space. The method in designing green open space with the theme of Agro Park is the method of the glass block design process with the following stages: data collection, analysis, synthesis, concept formulation and pre-design. Based on the results of data processing, analysis and synthesis, the basic ideas of development are: 1Integrating Green Open Spaces with functions and activities around the park, 2Maximizing the ecological functions of Green Open Spaces. Agro park is a theme that is determined as a response to the existing environmental conditions of the site which is located between community plantations and close to the Agricultural Extension Center Office so that it will become an integrated part to create an agricultural and plantation area for the people around it. Zonning Agro Park is divided into 1Zone for main, companion and supporting plants and 2Zones for social activities and entertainment. The functions that are accommodated are: ecological, social/cultural, educational and aesthetic. Circulation consists of the concept and design of circulation of the garden with the surrounding environment and the concept and design of circulation between zones within the Park. Types of vegetation based on the criteria for environmental parks and city parks according to the theme are the main plants consisting of: vegetables, bean plants, family medicinal plants, spice plants, and supporting plants consisting of: Flower and Leaf Plants, Shade Plants, Surface Cover Plants, plants barrier.Keywords: Agro Park, Green Open Space; North Gorontalo ABSTRAKRuang terbuka hijau (RTH) sebagai paru-paru kota merupakan salah satu aspek berlangsungnya fungsi daur ulang antara gas karbondioksida (CO2) dan oksigen (O2). Fungsi lain RTH diantaranya fungsi estetika, rekreasi dan ruang interaksi sosial antar masyarakat. Agro Park RTH di Kecamatan Tomilito Kabupaten Gorontalo Utara bertujuan untuk mewujudkan ruang kota yang lebih berkualitas, indah, nyaman, tertata, sehat dan berkelanjutan. Metode dalam mendesain RTH dengan tema Agro Park adalah metode proses desain glass block dengan tahapan: Pendataan, Analisis, sisntesis, rumusan konsep dan pra design. Berdasarkan hasil pengolahan data, analisis dan sintesis maka ide dasar pengembangan adalah: 1Mengintegrasikan Ruang Terbuka Hijau dengan fungsi dan aktifitas disekitar taman, 2Memaksimalkan fungsi ekologi Ruang Tebuka Hijau. Agro park adalah tema yang ditentukan sebagai respon terhadap kondisi eksisting lingkungan site yang berada di antara perkebunan masyarakat dan dekat dengan Kantor Balai Penyuluh Pertanian sehingga akan menjadi bagian yang saling terintegrasi untuk mewujudkan sebuah kawasan pertanian dan perkebunan bagi rakyat di sekitarnya. Zonning Agro Park terbagi atas 1Zona untuk tanaman utama, pendamping dan pendukung dan 2Zona untuk aktifitas sosial dan hiburan. Fungsi yang diwadahi adalah: ekologis, sosial/budaya, edukatif dan estetika. Sirkulasi terdiri dari konsep dan desain sirkulasi taman dengan lingkungan sekitar dan konsep dan desain sirkulasi antar zona di dalam Taman. Jenis vegetasi berdasarkan kriteria taman lingkungan dan taman kota sesuai tema adalah tanaman utama yang terdiri dari: sayuran, tanaman kacang, tanaman obat keluarga, tanaman rempah, dan Tanaman Pendukung yang terdiri dari: Tanaman Bunga dan Daun, Tanaman Peneduh, tanaman Penutup Permukaan, tanaman Pembatas.Kata kunci: Agro Park, Ruang Terbuka Hijau; Gorontalo Utara